VOLLEYBALL EVOLUTION. ASPECTS IN THE DEVELOPMENT OF THE ROMANIAN VOLLEYBALL - Ioan AUGUSTIN; Andrei DRAGOMIR; Alexandru MURESAN (Cluj University Press, 2015)
This scientific article presents the inception, evolution and the development of the volleyball game as it happened in time, due to the geopolitical and social influences. Though it appeared in the US it quickly spread worldwide due to a consistent and sustained promotion, but also brought by the US military and the First World War. Romania contributed as well to the development of the game, being a founding member of the International Federation. Nowadays volleyball still is a fashionable game, present in Olympics and all major sports competitions. Evoluția jocului de volei. Aspecte în dezvoltarea voleiului în Romania. Acest articol științific prezintă debutul, evoluția și dezvoltarea jocului de volei, așa cum a avut loc în decursul timpului, datorită influențelor de natura geopolitică și socială. Deși a apărut în US, acesta s-a răspândit în toată lumea atât datorită promovării consistente și susținute cât și prin detașarea trupelor militare americane în decursul primului razboi mondial. Romania a contribuit și ea la dezvoltarea jocului de volei, fiind membru fondator al federației internaționale, participantă la Jocurile Olimpice si la toate competițiile majore. Cuvinte cheie: debut, evoluție, dezvoltare, jocul de volei.